The Urgency of Understanding the Age of Marriage To Realize The Quality Of Education For Cadests In Puguh, Boja, Kendal - Dian Latifiani; Anis Widyawati; Muslikah; Seni Ira Maya Rasidah; Rahmawati Melati Sani; Choirul Fuad (Semarang State University Undergraduate Law and Society Review, 2025)
Child marriage is marriage under the recommended age by law, namely 19 years. Kendal Regency is an area with a high child marriage rate. This is shown by the Kendal PA Statistics Data, 2022 requests for dispensation for marriage, namely 253 in 2021 and 348 in 2022. One of the areas with a high marriage rate is Boja District. The rise of child marriage in Boja District is caused by various factors, including the sophistication of technology, communication information, low economic level, and promiscuity. The methods used are the lecture method, and the question-and-answer method. Measurement of the level of understanding is carried out by pre test and post test. The results of the service revealed that the level of understanding of members of the Puguh Village Karang Taruna regarding child marriage was quite good, but in terms of the minimum age limit for marriage there were still many mistakes. If a child's education is forced to drop out of formal school, then the right treatment is to continue to non-formal school through the Independent Learning Activity Center (PKBM).